Before the uprising : Hungary under communism, 1949-1956 - Kenez, Peter, 1937- 1937- (Cambridge University Press, 2022)
The years of 1949-1956 could be described as the gloomiest in modern Hungarian history, as the country's population lived under vicious totalitarian leadership. Eventually, the regime began to disintegrate, leading to the 1956 Hungarian Revolution - a critical moment in the history of the Cold War. But why did this revolution occur in Hungary, rather than any other countries in the Soviet bloc? Before the Uprising examines the specific social, economic, political, and intellectual characteristics of a totalitarian country. Throughout the volume, Peter Kenez questions what the necessary components of totalitarianism are: whether it is a complete state control of the economy, a personality cult of the leader, or a specific type of propaganda organization. By describing the totalitarianism of the past, this volume show what we can learn for the present, and what to expect from the emerging autocracies of the future